Hydrodynamic Shape Optimization for Naval Vehicles - Wilson, W.; Gorski, J.; Kandasamy, M.; Takai, T.; Wei He; Stern, F.; Tahara, Y. (2010 DoD High Performance Computing Modernization Program Users Group Conference, 2010)
This effort is focused on hydrodynamic shape optimization with application to naval vehicles. At present this is mainly applied to US Navy surface combatant hull forms and related systems, however, this approach could also be applied to other marine applications. In addition, this effort is aimed at assessing the current use of hydrodynamic analysis tools as a part of the ship design process and the need to perform proper validation of the tools to provide confidence in their use.